Têmpera magazine: a mobile magazine-gallery for education and inclusion by providing a visual repertoire for students and researchers in places with precarious cultural equipment (Palíndromo, 2023)
This is a brief history of Tempera magazine: periodical on visual arts, launched in 2019, which has fourteen published editions (and the fifteenth in print). Tempera is characterized by an attractive format due to the magazine's visual and physical artistic quality (artistic graphic design, good printing, paper, etc.), in order to encourage a better immersion of readers in the works presented and, also, to make the magazine a collectible object. Tempera Magazine seeks, in an accessible way, to expand the dissemination of visual knowledge, being a cultural and social curation tool in times of mass media, social networks and post-truth, and which was created considering debates raised by Annateresa Fabris, Joan Fontcuberta and Lívia Aquino. With a nationwide scope, since it has an online version, it is aimed not only at visual arts teachers and students, but also at the general public who are interested in the visual arts. In this Article, we discuss what motivated its creation, its operation, organization and circulation.
Keywords: visual arts; graphic design; visual language; art publications; periodic magazine